The emerging role of metabolic regulation in the functioning of Toll-like receptors and the NOD-like receptor Nlrp3 - O'NEILL, LUKE ANTHONY JOHN; TANNAHILL, GILLIAN (Elsevier, 2011)
While it has long been suspected that inflammation participates in the pathogenesis of metabolic disorders such as the insulin resistance that occurs in type 2 diabetes, recent work suggests that this is not the only important interaction between metabolism and inflammation. Inroads into the understanding of the relationship between metabolic pathways and inflammation are indicating that signaling by innate immune receptors such as TLR4 and Nlrp3 regulate metabolism. TLRs have been shown to promote glycolysis, whilst Nlrp3-mediated production of IL-1? causes insulin resistance. A key role for the hypoxia-sensing transcription factor HIF1? in the functioning of macrophages activated by TLRs has also recently emerged. This review will assess recent evidence for these complex interactions and speculate on their importance for innate immunity and inflammation.
PUBLISHED
Keywords: Immunology; Toll-like receptors (TLRs)